THE DENSITY OF ANOPHELES ARABIENSIS (DIPTERA: CULICIDAE) IN CORRELATION TO MALARIA CASES AND SOME ENVIRONMENTAL FACTORS IN THREE VILLAGES AROUND WAD MEDANI TOWN - Mohamed, Abdalla Ibrahim A.; Ali A. Kehail, Mutaman (مجلة الجزيرة للعلوم الصحية; مجلد 5 عدد 1 (2009), 2009)
This work aimed at studying the population density of Anopheles arabiensis and the incidence of malaria, during July–December 2001 and 2002. The study was conducted in three villages, namely Kereba, Barakat and Hantoub. The mean temperature and amount of rain fall were also recorded during this study. The results showed that the species of Anopheles arabiensis (Larvae and Adults) were recorded in all villages. The numbers recorded for this vector species were higher during September, in Kereba and Hantoub villages and during August in Barakat village than during the other months, during 2001. In 2002, the means recorded for this species were higher during September and October in Kereba and during August and September in Barakat and Hantoub than during other months. The species were not recorded during November and December 2002 in all villages. The overall mean number of the vector recorded in all villages was higher in 2001 than in 2002. The number of malaria cases recorded in all villages was highly correlated with the number of vectors recorded and with the environmental factors (means temperature and the amount of rain fall), during 2001, the amount of rainfall was high and this may have led to the increase of the breeding sites, and hence, the malaria cases recorded. During both years the numbers of vectors and of the resulting malaria cases were higher in Kereba and Barakat villages, than in Hantoub village.